Determination of Chemical Composition, Mineral Contents, and Protein Quality of Poultry By-Product Meal - Najafabadi, Hossein Jahanian; Moghaddam, Hassan Nassiri; Pourreza, Javad; Shahroudi, Feridoon Eftekhar; Golian, Abolghasem (International Journal of Poultry Science, 2007)
In order to study the chemical composition, mineral contents and protein quality of poultry by-product meal (PBPM), 10 composed samples of PBPM produced in Iran were provided during two months sampling period from rendering units of three industrial poultry slaughter-houses. The proximate analysis showed that the average dry matter (DM), ether extract (EE), crude protein (CP), crude fiber (CF) and ash of the PBPM samples were 94.8, 23.4, 60.5, 0.90, and 9.3 percent, respectively. The average gross energy (GE) value for the PBPM samples was 5645 kcal kg-1. The average values of major elements including Ca, P, Na, K, Cl, Mg, and S were 3.51, 1.88, 0.52, 0.31, 0.74, 0.06, and 0.99 percent, respectively. The average values of trace elements including Fe, Cu, Mn, Zn, and Se were 623.2, 9.3, 16.5, 47.8, and 0.73 mg kg-1, respectively. Biological evaluation of protein quality was done by chicks fed a nitrogen-free basal diet (as negative control) or chicks fed semipurified diets containing 10 percent crude protein from the PBPM or Kilka fish meal (as positive control) as the sole source of dietary protein. The values of protein efficiency ratio (PER) and net protein ratio (NPR) showed significant differences (p<0.05) among the PBPM samples and varied between 1.45 to 2.05 and 2.31 to 2.87, respectively. The PER and NPR values for the PBPM samples were significantly lower (p<0.05) than that of Kilka fish meal.